HIV testing algorithm KENPHIA 2018. - Raphael O. Ondondo (6429656) (2024)
Background Sub-Saharan Africa region bears the highest chronic hepatitis B virus (HBV) infection burden worldwide. National estimates of HBV burden are necessary for a viral hepatitis program planning. This study estimated the national prevalence of HBV infection in Kenya among people aged 15–64 years. Methods Of 27,745 participants age 15–64 years in the Kenya Population-based HIV Impact Assessment (KENPHIA) 2018 household survey, we analyzed data for all persons living with HIV (PLHIV; n = 1,521) and a random sample of HIV-negative persons (n = 1,551), totaling to 3,072 participants. We tested whole blood samples for hepatitis B surface antigen (HBsAg) using Determine™ HBsAg rapid test and used population projections to estimate national disease burden. Pearson chi square was performed and the weighted prevalence proportions presented. Findings Of the 3,072 participants,124 tested HBsAg positive, resulting in a weighted national HBV prevalence of 3.0% (95% CI: 2.2–3.9%). This translated to an HBV infection burden of 810,600 (95% CI: 582,700–1,038,600) persons age 15–64 years in Kenya. Distribution of HBV prevalence varied widely (p<0.001) by geography, ranging from 0.1% in Eastern Kenya regions to over 5% in northern and western Kenya. Prevalence of HBV infection was higher in PLHIV (4.7%; 95% CI: 3.3–6.0%) compared to HIV-negative persons (3.0%; 95% CI: 2.1–3.9%), and was highest among persons: age 45–54 years (6.4%; 95% CI: 3.3–9.5%), those who reported no formal education (10.7%; 95% CI: 5.1–16.4%), in polygamous marriages (6.8%; 95% CI: 1.7–11.8%), and in the lowest wealth quintile (5.3%; 95% CI: 2.8–7.7). When adjusted for covariates, lack of formal education (aOR = 4.2; 95% CI: 1.5–12.6) was significantly associated with HBV infection. In stratified analysis by HIV status, residing in rural areas and history of blood transfusion were independently associated with HBV infection among PLHIV, while lack of formal education and no history of blood transfusion were associated with HBV infection among HIV-negative participants (p<0.05). Interpretation HBV prevalence among persons aged 15–64 years in Kenya was 3.0%. Higher prevalence was documented among persons without formal education, in the lowest wealth quintile, and those living in Kenya’s North-Eastern, Rift Valley-North and Nyanza regions. Targeted programmatic measures to strengthen interventions against HBV infections including newborn vaccination and treatment of infected adults to limit mother-to-child transmission, would be helpful in reducing burden of HBV-associated viral hepatitis.